A Assistance in the use of web based library information systems at As Salam Garut Vocational School - Budiman, Tedi; Fawaz, Muhamad Fathur; Sidiq, Purnomo; Juliansyah, Tri Endriardi; Irawan, Irawan (Indonesian Journal of Community Empowerment (IJCE), 2023)
The purpose of this pkm is to build and develop a digital library school at SMK AS-SALAM which may offer more effectivity and efficiency of managing the school’s library. The method used on this research is waterfall method, one of methodologies which refers to waterfall, in this case each phase goes downward systematically, they are requirements, design, implementation, verification and maintenance. Information system digital library school provides librarian to manage certain processes such as user management, book management, book reserve, book history, stock book report, book reserve report and book fines report. The system works well for administrator and members which are students and teachers. Every member would get the system access if administrator inputs members data. Therefore, librarian would be able to maximize their jobs in library with short amount of time than use traditional way such as write report or create library members card.